Regional differences in waiting time to pregnancy: pregnancy-based surveys from Denmark, France, Germany, Italy and Sweden - Juul, S.; Karmaus, W.; Olsen, J. (Human Reproduction, 1999)
The objective of this study was examine geographical variation in couple fecundity in Europe. The study was based upon all recently pregnant (or still pregnant) women within well-defined geographical areas in Europe (Denmark, Germany, Italy, Sweden and France) at a given time period in 1992. Altogether, 4035 women responded to a highly structured questionnaire. Highest fecundity was found in Southern Italy and Northern Sweden; lowest fecundity was seen in data from the East German centre. Approximately 16% of the study population had a waiting time of more than 12 months to become pregnant. Most of the pregnancies were planned (64%) and approximately 14% were the result of contraceptive failures. The study shows that smoking, body mass index, age and parity did not explain the differences in fecundity found between the centres. Regional differences in fecundity exist and the causes may be genetic or due to variations in behavioural and environmental exposures.